Bank Lending, Bank Capital Regulation and Efficiency of Corporate Foreign Investment - Diemo Dietrich; Achim Hauck (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2007)
In this paper we study interdependencies between corporate foreign investment and the capital structure of banks. By committing to invest predominantly at home, firms can reduce the credit default risk of their lending banks. Therefore, banks can refinance loans to a larger extent through deposits thereby reducing firms' effective financing costs. Firms thus have an incentive to allocate resources inefficiently as they then save on financing costs. We argue that imposing minimum capital adequacy for banks can eliminate this incentive by putting a lower bound on financing costs. However, the Basel II framework is shown to miss this potential. – – In diesem Beitrag wird ein Bankenmodell entwickelt, um die Wechselbeziehungen zwischen Unternehmensauslandsinvestitionen und der Kapitalstruktur der finanzierenden Banken zu untersuchen. Es wird gezeigt, dass Multinationale Unternehmen einen Anreiz haben, ineffizient zu investieren, um Finanzierungskosten einzusparen. Der Grund ist, dass eine höhere Depositenrefinanzierung der Bank zwar die Finanzierungskosten senkt, jedoch das Unternehmen dazu zwingt, vornehmlich im Heimatland zu investieren. Es zeigt sich, dass eine Regulierung des Bankkapitals diese Ineffizienzen eliminiert, da durch sie eine Untergrenze für die Finanzierungskosten gesetzt wird. Allerdings stellen sich die neuen Baseler Regeln als unzureichend heraus, um dieses Potential auszuschöpfen.
urn:nbn:de:gbv:3:2-373
Keywords: G21; F23; G28; 330; financial contracting; multinational corporations; internal capital markets; Direktinvestition; Kapitalkosten; Bank; Kapitalstruktur; Eigenkapitalvorschriften; Theorie